The Best Time for EEG Recording in Febrile Seizure - KARIMZADEH, Parvaneh; REZAYI*, Alireza; TOGHA, Mansoureh; AHMADABADI, Farzad; DERAKHSHANFAR, Hojjat; AZARGASHB, Eznollah; KHODAEI, Fatemeh (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Karimzadeh P, Rezayi A, Togha M, Ahmadabadi F, Derakhshanfar H, Azargashb E, Khodaei F. The Best Time for EEG Recording in Febrile Seizure. Iran J Child Neurol. 2014 Winter; 8(1):20-25. Objective Some studies suggest that detection of epileptic discharge is unusual during the first postictal week of febrile seizure and others believe that EEGs carried out on the day of the seizure are abnormal in as many as 88% of the patients. In this study, we intend to compare early and late EEG abnormalities in febrile seizure. Materials & Methods EEG was recorded during daytime sleep, 24-48 hours (early EEG) and 2 weeks (late EEG) after the seizure in 36 children with febrile seizure (FS), aged between 3 months and 6 years. EEGs that showed generalized or focal spikes, sharp, spike wave complex, and slowing were considered as abnormal EEG. Abnormalities of the first EEG were compared with those of second EEG. Results The most common abnormal epileptiform discharges recorded in the early EEG were slow waves (27.6%) and sharp waves in late EEG (36%). Distribution of abnormalities in early and late EEG showed no significant statistical difference. Conclusion The early and late EEG recording had the same results in patient with febrile seizure. Reference: Hauser WA, Kurland LT. The epidemiology of epilepsy in Rochester, Minnesota, 1935 through 1967. Epilepsia 1975;16(1):1-66. Freeman JM. Febrile seizures: a consensus of their significance, evaluation, and treatment. Pediatrics 1980;66(6):1009. Waruiru C, Appleton R. Febrile seizures: an update. Arch Dis Child 2004;89(8):751-6. ILAE. Guidelines for epidemiologic studies on epilepsy, International League against Epilepsy. Epilepsia 1993;34(4):592-6. Annegers JF, Hauser WA, Shirts SB, Kurland LT. Factors prognostic of unprovoked seizures after febrile convulsions. N Engl J Med 1987;316(9):493-8. Berg AT, Shinnar S, Darefsky AS, Holford TR, Shapiro ED, Salomon ME, et al. Predictors of recurrent febrile seizures. Arch Pediatr Adolesc Med 1997;151(4):371-8. Nelson KB, Ellenberg JH. Predictors of epilepsy in children who have experienced febrile seizures. N Engl J Med 1976;295(19):1029-33. Anonymous. Practice parameter: the neurodiagnostic evaluation of the child with a first simple febrile seizure. American Academy of Pediatrics. Provisional Committee on Quality Improvement, Subcommittee on Febrile Seizures. Pediatrics 1996;97(5):769-72; discussion:773-5. Rosman NP. Evaluation of the child who convulses with fever. Paediatr Drugs 2003;5(7):457-61. Kanemura H, Mizorogi S, Aoyagi K, Sugita K, Aihara M. EEG characteristics predict subsequent epilepsy in children with febrile seizure. Brain Dev 2012;34(4):302-7. Yamatogi Y, Ohtahara S. EEG in febrile convulsions. Am J EEG Techno1 1990;30:267-80. Aicardi J, Chevrie JJ. The significance of electroencephalographic paroxysms in children less than 3 years of age. Epilepsia 1973;14(1):47-55. Tsuboi T. Seizures of childhood: a population-based and clinic based study. Acta Neurol Scand Suppl 1986;110:1-237. Maytal J, Steele R, Eviatar L, Novak G. The value of early postictal EEG in children with complex febrile seizures. Epilepsia 2000;41(2):219-21. Joshi C, Wawrykow T, Patrick J, Prasad A. Do clinical variables predict an abnormal EEG in patients with complex febrile seizures? Seizure 2005;14(6):429-34. Lennox-Buchthal M. Febrile convulsions: a reappraisal. Electroencephalogr Clin Neurophysiol 1973;32:Suppl:1-138. Frantzen E, Lennox-Buchtal MA, Nygraad A. Longitudinal EEG and clinical study of children with febrile convulsions. Electroencephalogr Clin Neurophysiol 1968;24(3):197-212. Kajitani T, Ueoka K, Nakamura M, Kumanomidou Y. Febrile convulsions and rolandic discharges. Brain Dev 1981;3(4):351-9. Sofijanov N, Emoto S, Kuturec M, Dukovski M, Duma F, Ellenberg JH, et al. Febrile seizures: clinical characteristics and initial EEG. Epilepsia 1992;33(1):52-7.